The Issue of Foreign Trade of Tashkent in Archival Documents (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the coverage of foreign trade relations of Tashkent on the basis of the analysis of archival documents. For this purpose, on the example of documents stored in the funds of the National Archives of Uzbekistan, the importance of the city of Tashkent in domestic and foreign trade, types of goods exported for domestic and foreign trade, prices, units of measurement, and customs duties on trade goods are analyzed. In addition to intensive domestic trade and economic relations within the Central Asian khanates, Tashkent was the main city with trade relations with the Eurasian nomadic pastoral region and near and far abroad, including China, the European and Siberian parts of Russia, East Turkestan, and Zhetysu. The role of craftsmen living in the neighborhoods of Tashkent, which specialize in the production of certain goods, was significant in the trade relations of Tashkent. Therefore, the neighborhood is called by the same product name, depending on which product it is adapted to produce. For example, "knife," "coppersmith," "archer," "tanner," saddle, etc. The article analyzes the prices of goods exported from Tashkent, their quantity, in what vehicles they were transported, and the collected customs duties.